(NmEHANIZACIQ LESOPOSADO^NYH RABOT (B/s - (N~ERNY[EW(B, (NwALENTIN wASILXEWI^(B.s ((NmOSKWA (B:s (NlESNAQ PROMY[LENNOSTX(B,s, 1978)
[ (NoPISYWAETSQ KLASSIFIKACIQ(B, (NKONSTRUKCIQ(B, (NTEHNI^ESKAQ HARAKTERISTIKA(B, (NRAS^ET PARAMETROW (B].s
(NbIBLIOGR(B.: 24 (NNAZW(B.s
Keywords: (NmEHANIZACIQs; (NlESOPOSADO^NYE RABOTYs; (NlESNAQ PROMY[LENNOSTXs